Strategic Human Resource Development A Journey in Eight Stages - Meifert, Matthias T. (Management for Professionals,, 2013)
In an era that has brought new and unexpected challenges for virtually every company, one would be hard-pressed to find any responsible manager who is not thinking about what the future will bring. In the wake of these challenges, strategic planning has moved from being the reserve of large corporations to becoming an essential need for even small and medium-sized enterprises. But what good is even the most convincing strategic concept if the companyỚ"s people are unwilling or unable to put it into practice? The key is to develop people, and to develop them not only for the work of today, but also for the challenges that the future holds. Strategic HR development has become a decisive force for the success of any business. This book, edited by Matthias T. Meifert, shows us which basic considerations we need to remember and what strategic HR development means in practice. Its interesting and vivid approach takes the reader on a tour of the eight stages of HR development, introduces the critical factors, and highlights many practical recommendations for strategic HR development practice in business. The second℗ German edition picks up on the popular original edition of 2008 and revises it to match recent developments. Again, it has managed to square the circle of giving a forum to leading researchers in the field while leaving enough room for a close and vivid survey of the practitionerỚ"s experience with the topic. Anybody who wants to know what strategic HR development can mean and how it can be introduced in practice at a company cannot pass by this essential book. Professor Dr Dr h.c. Lutz von Rosenstiel, Chair of Organizational and Industrial Psychology, Ludwig-Maximilians-University of Munich.